Penguatan Digital Pedagogy Skills bagi Guru SMKS Handayani Gowa melalui Implementasi Edredo Berbasis Simulation-Based Learning - Nirmala, Putri; Agusnaya, Nurrahmah; Rosidah, Rosidah; Wahyudi, Wahyudi; Purnamasari, Wulan (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2025)
Training on the use of Edredo based on Simulation-Based Learning is designed to improve the digital pedagogy skills of teachers at SMKS Handayani Gowa. This activity was carried out as a response to the limited skills of teachers in implementing digital learning that is relevant to the demands of the 21st century. The training was conducted through the stages of pre-test, simulation of using Edredo, reflection, interactive discussion, digital project implementation, and post-test. The pre-test results showed that the participants' average digital pedagogy skills were low to moderate, with an average score of 2.08 to 3.17. After the training, there was a significant increase in post-test scores which ranged from 4.42 to 4.58. The results of paired samples t-test analysis showed a statistically significant difference between the pre-test and post-test scores (p < 0.001). The distribution of post-test scores centred in the high score range (4.0 to 5.0) showed an even distribution of skill improvement among the trainees. Documentation of the activities showed the participants' enthusiasm in following all stages of the training, from the simulation of using Edredo to the implementation of digital projects. Thus, the implementation of Edredo based on Simulation-Based Learning proved effective in significantly improving teachers' digital pedagogy skills at SMKS Handayani Gowa. This finding is expected to be a reference for the development of digital technology-based teacher training models in the era of the industrial revolution 4.0.